2002
DOI: 10.1088/0953-2048/15/3/312
|View full text |Cite
|
Sign up to set email alerts
|

Study of structure, transport, paramagnetic and ferromagnetic properties of La0.8Sr0.2Mn1−xZnxO3perovskite manganite

Abstract: La0.8Sr0.2Mn1−xZnxO3 perovskite manganite with x = 0, 0.01, 0.03, 0.05, 0.1, 0.15, 0.3, 0.5 and 0.75 has been prepared by the solid state reaction and investigated by structural, transport and magnetic measurements. The structural characterization of the samples has been done by x-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements. The x-ray powder diffraction results indicate a single phase for 0 < x < 0.5, confirming that zinc is incorporated on the Mn site. The lattice parameters (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It is noteworthy that some insulator-metal and paramagnetic-ferromagnetic transitions were characterized around 75 • C for x = 0.2. 27 The values of the elastic constants at room temperature are reported in Table 2. In order to verify the good reproducibility of Table 1 Porosities of the various LSM samples The impact of the porosity over the elastic modulus is shown in Fig.…”
Section: La 08 Sr 02 Mno 3 (Lsm)mentioning
confidence: 99%
“…It is noteworthy that some insulator-metal and paramagnetic-ferromagnetic transitions were characterized around 75 • C for x = 0.2. 27 The values of the elastic constants at room temperature are reported in Table 2. In order to verify the good reproducibility of Table 1 Porosities of the various LSM samples The impact of the porosity over the elastic modulus is shown in Fig.…”
Section: La 08 Sr 02 Mno 3 (Lsm)mentioning
confidence: 99%
“…Also the presence of the dangling bonds at the grain boundary gives rise to different physics when compared to the grain. Several authors have substituted different cations like Fe 3+ , Al 3+ , Ga 3+ , Zn 2+ and Cu 2+ at the Mn-site and have shown that Mn-site substitution severely affects the conduction mechanism as well as the magnetic properties [7][8][9][10][11][12] fewer results exist for higher valent ion substitution at Mn-site to see its effect on the transport properties [13,14]. Substitutions at Mn-sites in manganites, irrespective of their electronic and magnetic nature, lower the ferromagnetic transition temperature but to different extents.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the method used have been given previously by Sotirova et al [6]. The samples were prepared in the form of a disk of 10 mm diameter and 3 mm thickness.…”
Section: Methodsmentioning
confidence: 99%